The effects of tiger milk mushroom (lignosus rhinocerotis) on airway inflammation in murine models of allergic asthma - Muhamad, Siti Aminah (2020)
Allergic asthma is associated with chronic airway inflammation and progressive airway remodelling. Current medications are effective, but these drugs are mostly steroid-based medications and have side effects. Hence, natural products should be explored as an alternative for the management of asthma. The sclerotium of Lignosus rhinocerotis (Cooke) Ryvarden (Tiger Milk mushroom) is used traditionally to treat various illnesses including asthma. However, limited studies described the effect of this mushroom scientifically. Thus, this study was carried out to evaluate the effect of L. rhinocerotis extract (LRE) on airway inflammation, remodelling and airway hyper-responsiveness (AHR) in murine models of asthma. LRE was prepared by hot water extraction method using soxhlet. This study was conducted in two different types of animal models; Ovalbumin (OVA)-challenged model and house dust mite (HDM)-challenged model. To established chronic model of asthma, female Balb/C mice were sensitised with two intraperitoneal (i.p) injections on day 0 and 7 and further challenged with OVA-inhalation for three times per week for 2, 6 and 10 weeks. Treatments of LRE (125, 250, 500 mg/kg) and dexamethasone (3 mg/kg) were given orally upon after every challenged. One group of mice were left without any allergen challenged after week 10 until week 12. Bronchoalveolar lavage (BAL) fluid was collected for cytokine analysis, serum for immunoglobulin E (IgE), lungs for histopathological analyses and lymph nodes (LN) for cell subsets analysis. Meanwhile, AHR study was carried out; HDM-model in response to methacholine (Mch) concentrations. Mice were sensitised on day 0, followed by daily HDM intranasal challenge on day 7-11, and treatment were given one hour prior to challenge. On day 14, the mice were anesthetised and tracheotomy was performed. The findings demonstrated LRE treatments (125, 250 and 500 mg/kg) significantly inhibited the production of goblet cell and thickness of airway smooth muscle (p<0.05) throughout the prolonged OVA-challenged. Wheras, 500 mg/kg LRE showed the most effective in reducing the expression of TGF-β1 and activin A in the remodelled airways. Moreover, this study showed that different dosages of LRE showed different patterns of suppression on inflammatory cells in BALF fluid, IgE level as well as Th2 cytokines throughout the weeks. In contrast, flow cytometry analysis revealed that LRE did not significantly reduce the percentages of CD3+CD4+ and CD3+CD8+ T-cells (p>0.05). For AHR study, LREtreated group significantly attenuated the level of airway resistance at 8-32 mg/ml Mch concentrations (p<0.05). In conclusion, these findings suggested that LRE could suppress airway inflammation, remodelling and AHR in mouse model of asthma; thus suggesting its therapeutic potential as an alternative for the management of allergic asthma.